Seasonal changes of macroalgae assemblages on the rocky shores of the Cape Horn Biosphere Reserve, Sub-Antarctic Channels, Chile - Ojeda Villarroel, Jaime Andrés; Marambio Gallardo, Johanna Valeska; Rosenfeld, Sebastian; Contador Mejias, Tamara Andrea; Rozzi Marin, Ricardo Roberto; Mansilla Muñoz, Andres Omar (My University, 2019)
The Magellanic Sub-Antarctic Channels ecoregion supports one of the greatest number of macroalgae species in South America. In this ecoregion, the majority of macroalgae research has been associated with spatial ecology. In contrast, the temporal scale has received little attention. Here, we report the seasonal changes of taxa richness, wet biomass and assemblage structure for intertidal macroalgae in Robalo Bay (55 degrees S), situated within the Cape Horn Biosphere Reserve. Overall, forty-nine macroalgae taxa were identified. We found a higher taxa richness and wet biomass in the summer than in the winter, but the strength of seasonal variations varied spatially across intertidal sites and levels. A similar seasonal pattern was detected with multivariate analysis. The seasonal changes are explained by the rise of seasonal algae such as Adenocystis utricularis. In turn, we found temporally-persistent algae such as Ceramium virgatum and Nothogenia fastigiata which did not show sharp seasonal variation. In conclusion, we suggest that macroalgal seasonality might be strongly modulated by coupled factors such as light, nutrient availability, sea surface temperature, relative humidity, and species composition. These factors would support an increase of taxa richness and wet biomass in the summertime on the rocky shores in high latitudes of South America.
Keywords: wet biomass; seaweeds; seasonal; sub-antarctic; rocky shore